Pediatric pharmacists' perspectives on essential skills and activities for community pharmacists caring for pediatric patients: A mixed-methods study. (September 2020) - Kelly, Jordan; Bengry, Tanner; Romanick, Marcel; Jupp, Jennifer; Dersch-Mills, Deonne
Background: Provision of care to pediatric patients represents a set of unique challenges for pharmacists. Pharmacists practising in pediatric-specialty areas (acute care or ambulatory) have unique perspectives on approaches to pediatric care that can be shared to support pharmacists less familiar with this group of patients in providing effective, patient-centred care. Methods: This was a mixed-methods study using data from pharmacist interviews to quantify and qualitatively describe the approaches to care most commonly reported by pediatric-specialty pharmacists when asked to provide advice to pharmacists on providing pharmaceutical care to infants and children. Data were coded in duplicate using an inductive approach, and discrepancies were resolved by consensus. The number of times a theme (or subtheme) was mentioned and the number of pharmacists who mentioned it were used as markers of the relative importance of the content. Results: The themes (and subthemes) that emerged as most important were clinical activities (dose checks, considering indication, using up-to-date height/weight), caregiver counselling (demonstrating measurement, discussing administration), medication safety (using consistent concentrations of liquids), compounded medications (risks of, use of caution), adherence (formulation considerations, palatability), avoiding use of over-the counter products (except analgesics/antipyretics) and use of external supports (colleagues, caregivers, resources). Conclusions: We present a collated and prioritized list of practical approaches for pharmacists to use when caring for pediatric patients across the spectrum of practice. Can Pharm J (Ott) 2020;153:xx-xx.